1986
DOI: 10.1126/science.3775377
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Transfer via Enzyme-Enzyme Complexes

Abstract: The concentrations of enzyme sites in cells are usually higher than the concentrations of cognate intermediary metabolites. Therefore metabolic pathways or substantial segments of pathways may proceed by the direct transfer of metabolites from one enzyme site to the next by means of enzyme-enzyme complex formation. This mechanism of metabolite transfer differs from that usually assumed where dissociation and random diffusion of metabolite through the aqueous environment is responsible for the transfer to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(124 citation statements)
references
References 28 publications
(40 reference statements)
2
121
0
1
Order By: Relevance
“…Assuming an average mammalian cellular protein content of ~0.75 ng (76), and an average volume of ~4 x 10 -12 liter (1), there would be ,~109 actin molecules/cell (72). This results in a cellular actin concentration of "d9 mg/ml, consistent with a total cellular protein concentration of '~ 200 mg/ml (66,67). If we assume that approximately half the total cellular volume is cytoplasmic, due to the volume fraction of mitochondria, vesicles, and endoplasmic reticulum, then the net actin concentration would be ,,040 mg/ml, or 900 tiM.…”
Section: How Much Aldolase Is In Cells?mentioning
confidence: 70%
“…Assuming an average mammalian cellular protein content of ~0.75 ng (76), and an average volume of ~4 x 10 -12 liter (1), there would be ,~109 actin molecules/cell (72). This results in a cellular actin concentration of "d9 mg/ml, consistent with a total cellular protein concentration of '~ 200 mg/ml (66,67). If we assume that approximately half the total cellular volume is cytoplasmic, due to the volume fraction of mitochondria, vesicles, and endoplasmic reticulum, then the net actin concentration would be ,,040 mg/ml, or 900 tiM.…”
Section: How Much Aldolase Is In Cells?mentioning
confidence: 70%
“…These approaches are thus prone to two types of errors. First, they underestimate the functional consequences of modulating gene expression, especially for the many enzymes (19,47) whose normal activities have little influence on the steady-state flux of the embedding pathways. ‡ ‡ Second, they incorrectly predict that similar functional consequences ensue when changes in any two enzymes of the same metabolic branch yield the same change in flux.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical calculations for a simple unbranched pathway (A.S. and M.A.S., unpublished data) and numerical results for a simple model pathway that was parameterized to resemble glycolysis (49) indicate that up-regulation of the equilibrium and downstream nonequilibrium enzymes achieves increased flux without the previous disadvantages. In metabolic engineering, it has also been found that large increases in some enzyme activities intended to ‡ ‡ If, as seems likely, the glycolytic pathway represents the typical situation, most enzymes are excess-activity enzymes, and these are usually also the most abundantly expressed enzymes in each pathway (19,47). Much, if not most, of the cellular protein with enzymatic activity may thus be fulfilling functional requirements other than flux capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in this expression U, and U , have the same value as in expression (20). The identity of U, in these two expressions implies that the ideal free energy of the dissociation of the complex into its constitutive enzymes be the same whether the enzyme El has bound the transition state S' or the transition state Xf.…”
Section: Thermodynamic Significance Of Generalized Microscopic Reversmentioning
confidence: 93%
“…Eqn (20) above would be equally valid if the association of the two enzymes were destabilizing the ground and (or) the transition states.…”
Section: Thermodynamic Significance Of Generalized Microscopic Reversmentioning
confidence: 99%